Membangun Kerukunan Umat Beragama Dengan Nilai-Nilai Pluralisme Gus Dur - Rohman, Fathur; Munir, Ahmad Ali (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2018)
This article tries to explain the application of Abdurrahman Wahid's or Gus Dur's pluralism values to build harmony between religious groups. The late Gus Dur was recognized as representing one of the leaders of pluralism activists in Indonesia. Because of his commitment, gait, and his thoughts on pluralism he was dubbed the father of Indonesian pluralism. For Gus Dur, pluralism is the main key to building a pluralistic Indonesian society. Support the struggle to equalize or unite religions, recognize the truth of other religions by taking an active role in achieving common goals. Tolerance that only emphasizes the acceptance or recognition of the freedom of worship of other religions is not strong enough to be the foundation of harmony. Tolerance is still quite vulnerable and risky from infiltration and divisive propaganda. To build harmony, a sincere intention is needed for dialogue and productive communication across religions. It is not enough to arrive at that, interfaith dialogue must also be realized in the form of cooperation between religious communities to achieve strong harmony based on plurality.